Primary Hydatid Cyst of Parotid Gland: A Rare Case Diagnosed by Computed Tomography - Hassan, Qays A. (AL-Kindy College Medical Journal, 2019)
Hydatid disease is a zoonotic infection caused by Echinococcus species. The cystic form of this infection mostly involves liver and lung. Hydatid disease of the parotid gland even in endemic regions is a very rare entity that may be easily overlooked in daily practice. Herein, I present a case report of a 60-year-old Iraqi female patient who presented with a progressively painless mass in her right parotid. It was diagnosed radiologically as a hydatid cyst and was excised successfully. Histopathologic examination of the resected specimen confirmed the hydatid cyst. This case emphasizes the importance of considering hydatidosis in the differential diagnosis of any parotid mass, especially in endemic countries.